"It's not very feminine to have a mustache": Experiences of Danish women with polycystic ovary syndrome. Issue 2 (1st February 2017) - Pfister, Gertrud; Rømer, Kristine
ABSTRACT: This article explores women's lived experiences with polycystic ovary syndrome (PCOS) on the basis of semistructured interviews with 21 Danish women. It provides insights about the problems that they experienced and how they coped with PCOS. The interviews revealed that they were highly influenced by society's femininity norms. Many of them perceived their bodies as "different" because of the symptoms of PCOS, namely, hirsutism. They used different strategies to live up to body ideals and cope with the symptoms. However, hirsutism had a decisive negative influence on the women's everyday lives, particularly with regard to male partners and sexual relations.